Effects of Forestry Waste Neolamarckia cadamba Leaf Meal as an Additive on Fermentation Quality, Antioxidant Activity, and Bacterial Community of High-Moisture Stylo Silage - Wu, Shuo; Gao, Lin; Chen, Dandan; Xue, Yanlin; Kholif, Ahmed E.; Zhou, Wei; Chen, Xiaoyang; Zhang, Qing (Frontiers in Environmental Science, 2022)
N. cadamba leaves, a byproduct of wood production, are always discarded in the field. N. cadamba leaves have strong antibacterial property, which might be recycled to inhibit undesirable bacteria and enhance the fermentation quality of silage. Ensiling, a traditional conservation method for animal feed, is commonly used all over the world. It is known that high-moisture forages, especially legumes, are difficult to ensile directly as much ammonia-N and butyric acid produced by undesirable bacteria will reduce the feeding value. To investigate the effects of N. cadamba leaf meal on the fermentation quality of stylo silage, 5% and 10% N. cadamba leaf meal were mixed with stylo for 30 days of ensiling in two independent experiments. Results showed that the silage pH and butyric acid content of stylo silage were decreased (p < 0.01) by 10% N. cadamba leaf meal. In experiment 2, contents of nonprotein-N and ammonia-N were significantly decreased (p < 0.05), while the true protein content was significantly increased (p < 0.05). The same results on the changing tendency were also obtained in experiment 1. In addition, N. cadamba leaf meal addition also decreased the bacterial diversity. The relative abundance of Clostridium and Lelliottia decreased, whereas that of Lactobacillus increased when N. cadamba leaf meal was added. It is worth noting that the addition of N. cadamba leaf meal also improved the antioxidant activity of stylo silage. The aforementioned results suggested that mixing N. cadamba leaf meal to high moisture forages could be an effective strategy to enhance silage fermentation quality, and it is also a feasible way to recycle N. cadamba leaves.